Mechanistic insights into the pathways of phenol hydrogenation on Pd nanostructures - Porwa, Govind; Gupta, Shelaka; Sreedhala, S.; Elizabeth, Joes; Ithan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2019)
Product selectivity in aqueous phase phenol hydrogenation on well-defined supported Pd nanostructures (spheres, cubes, and octahedra) was studied using defined experiments and density functional theory (DFT) simulations. On Pd spheres and octahedra, the reaction initially showed high selectivity (in the first 3 h, at 363 K and 5 bar H-2 pressure) toward the partially hydrogenated product cyclohexanone. On prolonged operation (>20 h of reaction time), a shift in the product selectivity (up to 100%) toward the completely hydrogenated product cyclohexanol was observed on Pd spheres and octahedra. In contrast, the reaction on Pd cubes, which only had {100} facets, showed a high selectivity (similar to 90%) toward the product cyclohexanone even after 40 h, at the same reaction conditions. Since the {111} facets are expected to be the majority sites on a spherical particle, we attribute the selectivity trend observed on spherical Pd particles to be primarily controlled by the selectivity trend on the Pd{111} facets. This observation was further confirmed on performing the hydrogenation reaction on a mixture of Pd cube and Pd octahedron particles in a ratio of 25:75 (representing the site ratio of a spherical particle). DFT simulations provided a mechanistic insight into the reactivity of the two different facets ({100} and {111}) toward phenol hydrogenation. The calculations revealed that the selectivity significantly depended on the activation barriers involved in cyclohexanone hydrogenation on the Pd{111} facets (77 and 57 kJ/mol) as compared to those on the Pd{100} facets (97 and 101 kJ/mol).
Keywords: Cyclohexanol; cyclohexanone; facet-dependent reactivity; phenol hydrogenation

Pd nanoparticles supported on N-incorporated hybrid organosilica as an active and selective low-temperature phenol hydrogenation catalyst - Betsy, K. J.; Bajpai, Priyam; Lazar, Anish; Vanka, Kumar; Vinod, C. P. (ACS Applied Nano Materials, 2023)
A heterogeneous Pd-NPMO hybrid-silicacatalyst is synthesized andits application for aqueous phase selective hydrogenation of phenolto cyclohexanone at near ambient temperature (40 degrees C) and underatmospheric hydrogen pressure is demonstrated. The homogeneously distributedPd nanoparticles on N-bridged hybrid mesoporous organosilica showedremarkable activity and selectivity for cyclohexanone compared tothe unmodified Pd-SBA-15 catalyst. Control experiments strongly claimthe role of nitrogen domains in the organic framework of hybrid silicasupport in stabilizing small Pd nanoparticles and possibly modifyingthe Pd sites responsible for catalysis to activate the substrate moleculesin water. The hybrid silica catalyst was stable and reused severaltimes without any significant drop-in activity, proving the heterogeneityof the bifunctional Pd catalyst. Based on the density functional theorystudy and experimental interventions, a possible reaction mechanismfor the low-temperature phenol hydrogenation explaining the role oforganic domains in the hybrid-silica framework is proposed.
Keywords: cyclohexanone; Hybrid silica; palladium nanoparticles; Periodic mesoporous organosilica; phenol hydrogenation

Phenol hydrogenation to cyclohexanol catalysed by palladium supported on CuO/CeO2 - Kasabe, Mirabai M.; Kotkar, Vaibhav R.; Dongare, Mohan K.; Umbarkar, Shubhangi B. (Chemistry-an asian jounrnal, 2023)
Hydrogenation of phenol to cyclohexanone/cyclohexanol is an important reaction in production of nylon-6, nylon-66 and in petroleum industry. Liquid phase phenol hydrogenation over Pd-CuO/CeO2 was carried out under mild conditions. Palladium impregnated over CuO/CeO2 synthesized by co-precipitation method showed excellent catalytic activity for phenol hydrogenation (99% conversion with 80% cyclohexanol yield) at 90 degrees C and 10 bar H-2 pressure in water. Commercial 10%Pd/C showed only 8% phenol conversion under identical conditions. The detailed characterization revealed significant improvement in surface area of ceria after addition of CuO and decrease in crystallite size with creation of defects in CeO2 lattice. XPS analysis showed Pd loading on CuO/CeO2 to cause hydrogen spillover on the surface leading to increase in the oxygen vacancies. The interaction of phenol with catalyst surface studied by detailed FTIR analysis, revealed activation of phenol on oxygen vacancy of ceria as phenoxide ion with perpendicular orientation of aromatic ring on catalyst surface.
Keywords: Cyclohexanol; Hydrogen spillover; oxygen vacancies; Pd-CuO/CeO2; phenol hydrogenation